The Analysis of Moral Values in the Novel “the Midnight Library” - Jufiati, Jufiati (ASHLITION : Ash-Shahabah English Literature, Linguistics, & Education, 2024)
The study aims to find out how the main character reflects on himself and to find out people’s attitudes towards the main character in the novel “The Midnight library” The analysis of moral value in novel ‘The midnight library. The analysis used is the method of analysis data. The data in this research are words that contain moral values in the novel "The Midnight Library" by Matt Haig. The data obtained were analyzed using interactive model data analysis. The Data instrument is a tool used to collect data. In this research, the researcher acts as a key instrument in collecting data. Besides that, the researcher noted the moral values that exist in the novel under researcher. Notes are a tool that researchers use to collect data. Researchers used two sources of primary and secondary data. Primary data is the novel The Midnight Library written by Matt Haig. Secondary data is data sources that support this research such as journals, articles, related to novels, and websites. The data were analyzed using qualitative descriptive, namely research procedures with the results of presenting descriptive data in the form of researcher quotes in the novel The Midnight Library. After analyzing the novel The Midnight Library, the writer found six types of moral values such as Bravery, Honesty, Fortitude, Gratitude, Kindness, Trust word and care.